Indications for liver transplantation in patients with amyloidosis: a single-center experience with 11 cases - Singer, Reinhard; Mehrabi, Arianeb; Schemmer, Peter; Kashfi, Arash; Hegenbart, Ute; Goldschmidt, Hartmut; Schönland, Stefan; Kristen, Arnt; Dengler, Thomas; Müller-Schilling, Martina; Sauer, Peter; Dogan, Ayhan; et al. (Transplantation, 2005)
Familial amyloidotic polyneuropathy (FAP) is an inherited disorder with the systemic deposition of amyloid fibrils containing mutant transthyretin variants. The mutant form of transthyretin amyloidosis is produced mainly in the liver. Successful liver transplantation (LTx) could eliminate the source of the variant transthyretin molecule, and is now the only known curative treatment. The aim of this study is to evaluate the results of LTx for FAP at the University of Heidelberg. Eleven patients who underwent LTx between 1985 and 2004 with the diagnosis of FAP were evaluated. Of 11 patients, seven (64%) were male and four (36%) were female. The mean age was 49.5 years (range 27-70). Met 30 (n=5) was the most common type of amyloidosis followed by Arg 50 (n=3), Val 107 (n=2), and Phe 33 (n=1). All of the patients were selected for LTx and Domino LTx was performed in six patients. The majority (80%) of the patients with type Met 30 amyloidosis are alive, whereas in other types of amyloidosis only 33% are living. This finding emphasizes better prognosis of Met 30 variant of FAP in comparison to other variants such as Arg 50, Val 107, and Phe 33. After LTx, improvement of clinical symptoms (completely or partially) was observed in six patients (55%). In conclusion, LTx is considered as the only therapeutic alternative in patients with amyloidosis accompanied by hepatic synthesis of the amyloid protein. The most important risk factors for LTx can be predicted by assessing the nutritional condition of the patient, the duration of the disease, and the amyloid variant. Therefore, precise diagnostic measures are required before listing a patient for LTx. Domino LTx is an acceptable form of LTx that can preserve the pool of organ donors. In order to stop the progression of FAP, LTx would be justified in a subgroup of patients with amyloidosis. Based on our results, we support the idea that the effectiveness of extended preoperative period before LTx or the transplantation of other transthyretin variants other than Met 30 is questionable.
Gesehen am 04.02.2022